Dislocated Worker Human Capital Depreciation and Recovery - Kevin Hollenbeck; Richard J. Willke (W.E. Upjohn Institute for Employment Research, 1990)
Previous studies have estimated the "human capital depreciation" of women re-entering the work force after voluntary, lengthy interruptions. Those studies have found reduced real wages and furthermore the decrease is positively related to the length of the interruption. Upon re-entry, however, real wages grow rapidly as human capital is restored. This paper develops a model of the wage histories of dislocated workers. Similar to labor force re-entrants, those dislocated workers who become re-employed would experience wages below their final wage prior to dislocation and the decrease should be associated with the length of dislocation. However, the model suggests that since the career disruptions are involuntary and since occupational shifts generally occur, recovery will not be rapid nor complete. The model is estimated with data from a sample of workers in Ohio who had been dislocated and received services under Title III of the Job Training Partnership Act (JTPA). This data set has the limitation that the observations are for workers who chose to receive services, but it also has the advantage that the effects of a variety of training interventions on outcomes can be determined.
Keywords: J0; J6; 330; dislocated; workers; JTPA; Hollenbeck